PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS II SEKOLAH DASAR - Sri Widayanti; Vicky Dwi Wicaksono; Israfiana; Selviari; Satrio Budiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The independent curriculum is a curriculum that emphasizes that every student must learn according to their talents. Teachers must organize their lessons to accommodate learning according to the diversity of student skills. Many children still have difficulty understanding and mastering fraction material when learning mathematics. Thus, the purpose of this study was to determine whether the TaRL method in mathematics learning in class 2-A SDN Dukuh Kupang III, Surabaya City, can improve student learning outcomes. A total of 28 students in the class were the subjects of the study. The instruments used were tests and observations, using qualitative and quantitative data analysis. The results of the pre-cycle evaluation showed an average score of 51 with 7 students, or 25% of the total, having completed the lesson. The average score in cycle I was 70 and 19 students, or 68% of the total, had completed the lesson. In cycle II, the average normal score was 82.5 and 24 students, or 86% of the total, had completed the lesson. Based on the fulfillment of learning outcomes of more than 85% with a score of at least 70% according to the success indicators. Therefore, learning mathematics with the Teaching at the Right Level approach can be the right solution and an effective approach to improve learning outcomes.